Ancient ocean coastal deposits imaged on Mars - Jianhui Li; Hai Liu; Xu Meng; Diwen Duan; Haijing Lu; Jinhai Zhang; Fengshou Zhang; Derek Elsworth; Benjamin T. Cardenas; Michael Manga; Bin Zhou; Guangyou Fang (Proceedings of the National Academy of Sciences, 2025)
The northern lowlands of early Mars could have contained a significant quantity of liquid water. However, the ocean hypothesis remains controversial due to the lack of conclusive evidence from the Martian subsurface. We use data from the Zhurong Rover Penetrating Radar on the southern Utopia Planitia to identify subsurface dipping reflectors indicative of an ancient prograding shoreline. The reflectors dip unidirectionally with inclinations in the range 6° to 20° and are imaged to a thickness of 10 to 35 m along an uninterrupted 1.3 km northward shoreline-perpendicular traverse. The consistent dip inclinations, absence of dissection by fluvial channels along the extended traverse, and low permittivity of the sediments are consistent with terrestrial coastal deposits—and discount fluvial, aeolian, or magmatic origins favored elsewhere on Mars. The structure, thickness, and length of the section support voluminous supply of onshore sediments into a large body of water, rather than a merely localized and short-lived melt event. Our findings not only provide support for the existence of an ancient Martian ocean in the northern plains but also offer crucial insights into the evolution of the ancient Martian environment.